Optimasi Formulasi Body Lotion Berbasis Gelidium sp dengan Variasi Air Ekstraksi dan Setil Alkohol - Rafli Naufal; Nofita Rahmadani; Mahreni (JUSTER : Jurnal Sains dan Terapan, 2025)
Body lotions with synthetic chemicals can be replaced with natural ingredients such as agar from Gelidium sp., which functions as an emulsifier, thickener, and moisturizer. This study evaluates the impact of varying Gelidium sp. extract ratios and cetyl alcohol concentrations on the physical properties, stability, and user preferences of body lotion formulations. Formulations were prepared using five extract ratios (E1-E5) combined with six cetyl alcohol concentrations (F1-F6). Evaluations included pH measurement, viscosity testing, stability, homogeneity observation, and organoleptic testing. The results showed pH values ranging from 6.13 to 7.43 and viscosities between 2,000 and 60,000 cP, according to Indonesian National Standards (SNI). Stability testing confirmed no phase separation after six centrifugation cycles (3,600 rpm, equivalent to 7.2 months). Formulation F5 (8% cetyl alcohol) was the most preferred (35%), followed by F4 (6%, 25%). In conclusion, Gelidium sp. extract is suitable for body lotion formulations that comply with SNI standards. Formulation F5 demonstrated the highest consumer preference and has strong potential for further development.